Prevalence and Knowledge of Harmful Effects of Alcohol Consumption among Pregnant Women in Edo and Delta States, Nigeria. - Usifoh, Stella F.; Aika, Isabel N.; Ogugu, Oghenemine N.; Odili, Valentine U. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Alcohol consumption during pregnancy is a burden to public health as a common visible effect of alcohol use is fetal alcohol syndrome. The study determined the prevalence of alcohol consumption in pregnancy and knowledge of its harmful effects among the women in parts of Edo and Delta states of Nigeria. A cross-sectional study of 600 pregnant women with a structured questionnaire on demographics, consumption of alcohol and knowledge of the harmful effects on fetus were assessed. Many respondents 42% were within 21-29 years, married (90%) and 46.1% had tertiary education. More than half of the respondents 385(64.2%) have taken alcohol, 216(36%) before or 176(29.3%) during present pregnancy. Reasons given by 47 (7.8%) were to prevent spitting, nausea and vomiting, while twenty four (4%) of the respondents believed alcohol makes the baby small for delivery and 34 (5.6%) believed it makes them strong for daily activities. However, (55.7%) were unaware of its harmful effects and only 22 (3.6%) knew about fetal alcohol syndrome. Prevalence of alcohol intake is high 64.2% and is more in Delta than Edo State. Many of the pregnant women are unaware of the detrimental effects of alcohol to fetus especially fetal alcohol syndrome. There is need for educational campaigns on abstinence of alcohol among women of child-bearing age.